The complete mitochondrial genome of a parasitic flatworm Senga ophiocephalina (Cestoda: Bothriocephalidae). Issue 1 (1st January 2016) - Tang, Ju-Fen; Cai, Jia; Hang, Yu; Lin, Zi-Wei; Lu, Yi-Shan; Jian, Ji-Chang
Abstract: Mitochondrial DNA of nematodes undergoes frequent rearrangements, so it is a very good model for studying the mitochondrial genome evolution. The complete mitochondrial genome of a parasitic nematode Senga ophiocephalina was sequenced and annotated. The 13, 816 bp-long genome contained 12 protein-coding genes ( atp8 gene was missing), two ribosomal RNAs, 22 transfer RNAs, and a 391 bp non-coding region. Phylogenetic analysis showed that S. ophiocephalina forms a monophyletic cluster with the remaining two Bothriocephalidae species.